Engendering Democracy in Brazil. Women's Movements in Transition Politics / Sonia Alvares E. - Alvares E, Sonia (Estados Unidos de America: Princetion University Press, 1990)
Theoretical and comparative perspectives on women´s movements and the state, women in the new social movements of urban Brazil, militant mothers and insurgent daughters, women in the opposition to authorintarian rule, the rise and fall of a Unites, mass-base brazilian women´s movemet, approching the authoritarian states, women´s movements and population policy in trasitional brazilian politics, taking ferminis into the state, gender policy and the PMDB{s councils on the status of women.
Index
Col. Soc
Keywords: 1. WOMEN´S 2.WOMEN MOVEMENTS 3. POLITICS 4. MUJERES PROGRESO BRAZIL SOCIOLOGY